Foreign policy in comparative perspective domestic and international influences on state behavior - Beasley, Ryan K. (CQ Press, 2013)
In this much-anticipated revision of their unique text, the editors bring together fifteen top scholars to highlight the importance of both internal and external forces in foreign policymaking.